Model Ibadah dalam Tinjauan Tafsir Izwaji - Musthofa Musthofa (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
Worship according to the view of understanding the science of jurisprudence can be divided into two, namely mahdah worship, worship that is still pure setting of procedures, place and time and gairu mahdah worship, which is a model of worship that is not regulated by procedures, determination of time and place by sharia. The model of mahdah worship is prescribed: (1) bound by place, time and procedure, (2) bound by procedure, (3) bound by time limit on the circulation of the sun/moon. (4) Bound by procedure but not bound by time, place. The model of worship of gairu mahdah is a form of worship that is not pure in bond with Islamic law, both place, time and procedure (unless prescribed). Ibadah mahdah which is bound by place, time and procedure such as Hajj, is bound by time and procedure such as prayer, which is bound by procedure such as absolute sunnah fasting, Hajj. Gairu mahdah such as zikir, shadaqah, devotion to both parents.